If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5n(5n + -6) = 0 Reorder the terms: -5n(-6 + 5n) = 0 (-6 * -5n + 5n * -5n) = 0 (30n + -25n2) = 0 Solving 30n + -25n2 = 0 Solving for variable 'n'. Factor out the Greatest Common Factor (GCF), '5n'. 5n(6 + -5n) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0Subproblem 2
Set the factor '(6 + -5n)' equal to zero and attempt to solve: Simplifying 6 + -5n = 0 Solving 6 + -5n = 0 Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5n = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5n = 0 + -6 -5n = 0 + -6 Combine like terms: 0 + -6 = -6 -5n = -6 Divide each side by '-5'. n = 1.2 Simplifying n = 1.2Solution
n = {0, 1.2}
| 3r^2+3r-6=0 | | -2y=-4y+24 | | 6m^2-72+216=0 | | 2v^2-14v+12=0 | | 3x+2+6x+11+5x-1=180 | | 3y-2y(y+19)=9y-3(9-y) | | -6(4d+5)+7d=-2d | | 33y-6y=-18-36 | | -(p+17)=4p-2 | | 3x-15+2=-20 | | 10-16=12x-6x-3x-3 | | p+0.77=9.3 | | 0.3+0.6(25-c)=12 | | 5x-1=6x+11 | | 2.7h+15=0.3(10-h) | | y=4x^2-x^2 | | 200=3x+2 | | 5x-4-7x=3x+6 | | 200=3x+7 | | 9(8d*5)+13=12d-2 | | -15=-6+x | | 4r-10=2r+16 | | 5(4-2y)=8(3y-2) | | -3(6a-3)+8a=-1 | | 3.1t+7=2.6 | | 3x-6=8x-26 | | 0.8(y-5)=10 | | 5(3k-2)=4(3-5k) | | -9(2-y)-(2-y)=2 | | -x-4=3x-4 | | 6(2g-4)-(3g-7)=1 | | xy^4+x^2y=5x+3y |